Strategi Kesantunan Berbahasa Mahasiswa kepada Dosen pada Wacana Komunikasi Media Sosial Whatsapp - Sriyanti, Rini (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This study examines the politeness strategies employed by students when communicating with lecturers via the social media platform WhatsApp. Based on a literature review, it was found that students tend to apply positive politeness strategies by using warm greetings, formal language, and politeness markers such as "please" and "excuse me." Additionally, students adapt to digital technology features, such as emoji use and message timing, as a form of respect towards lecturers. These findings suggest that, despite WhatsApp's informal nature, students maintain politeness in their interactions with lecturers to preserve a positive relationship. The study highlights the importance of understanding digital politeness etiquette within academic communication.